Impact of prescribed opioid use on development of dementia among patients with chronic non-cancer pain - Tak Kyu Oh; In-Ae Song (Scientific Reports, 2024)
Abstract We aimed to examine the association between opioid use and the development of dementia in patients with chronic non-cancer pain in South Korea. Data were extracted from the National Health Insurance Service database in South Korea. Adult patients diagnosed with musculoskeletal diseases with chronic non-cancer pain between 2010 and 2015 were included in the analysis. Patients who were prescribed opioids regularly and continuously for ≥ 90 days were classified as opioid users. In total, 1,261,682 patients with chronic non-cancer pain were included in the final analysis, of whom 21,800 (1.7%) were opioid users. From January 1, 2016 to December 31, 2020, 35,239 (2.8%) patients with chronic non-cancer pain were newly diagnosed with dementia. In the multivariable model, opioid users showed a 15% higher risk of developing dementia than the control group. Additionally, opioid users showed a 15% and 16% higher risk of developing Alzheimer’s disease and unspecified dementia, respectively, than the control group, but did not show any significant differences for vascular dementia. Among adult patients with chronic non-cancer pain, opioid users were at a higher risk of developing dementia than the control group; the risk was significantly higher for Alzheimer’s disease but not for vascular dementia in this study. Our results suggest that in patients with CNCP, public health strategies should target opioid users for early dementia detection and intervention.